Analysis of Strengthening Environmental Awareness through the Adiwiyata Program - Putra, Try Andikha; A. Pratama, Fairuz; Nunung, Risna; E.K. Nuha, Farha; F. Az-zahra, Dita; D. Syahrani, Maura; Pujiatna, Tri (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2026)
Environmental degradation is a pressing global issue that demands systemic responses, including through formal education. This study investigates the implementation of the Adiwiyata Program at SDN Kalijaga Permai and its contribution to strengthening students' environmental awareness. A research gap exists in that previous studies have largely focused on administrative compliance and physical infrastructure of the Adiwiyata Program, while the internalization of environmental values and its direct impact on student behavior has received limited attention. This study addresses this gap by examining how habituation activities within the Adiwiyata Program shape actual student behavior. A qualitative case study approach was employed, with data collected through in-depth interviews with the school principal, Adiwiyata coordinator, and four teachers; participatory observations; and open-ended questionnaires distributed to 32 students. Data were analyzed using the Miles and Huberman model. The findings reveal that continuous habituation activities—encompassing waste management, cleanliness maintenance, greening programs, and teacher role modeling—positively contribute to the development of students' environmental awareness. However, inconsistencies remain in water conservation practices and independent student initiative. These findings highlight the need for a more values-oriented approach within the Adiwiyata framework to ensure deeper internalization beyond routine compliance.